Meadows and proportionality in judicial review - Where are we now? - Brady, Alan (My University, 2017)
In Meadows v Minister for Justice, Equality and Law Reform a 3:2 majority of the Supreme Court endorsed the use of a proportionality test in judicial review where the impugned decision engaged fundamental rights. For some time, there had been concern that the use of the ‘no relevant material’ version of the irrationality test as set out by the Supreme Court in O’Keeffe v An Bord Pleanala was too narrow to allow adequate protection for constitutional (and subsequently ECHR) rights in Irish Administrative Law.3However, after Meadows the position shifted. The nature and extent of that shift has not always been easy or straightforward to discern4andsomewhatcompeting lines of authority on how the proportionality test is to be applied seem to have emerged.The dominant strand has concerned immigration cases, where it seems to be settled that in administrative law cases where constitutional or ECHR rights are in issue,it is for the first instance decision-maker to apply the proportionality test; this is then subject to an irrationality review by the courts, using the Keegan standard. Conversely, some outlier cases in non-immigration matter have given an indication that it may be for the courts themselves to apply the proportionality test. The purpose of this paper is trace these developments and make some tentative suggestions on how Meadows proportionality is likely to develop, drawing some lessons from the development of the proportionality test in the UK under the Human Rights Act 1998.
Bar Council of Ireland - Judicial Review Update